The Aging Navigational System - Lester, Adam W; Moffat, Scott D; Wiener, Jan M; Barnes, Carol A; Wolbers, Thomas (Neuron (Cambridge, Mass.), 2017)
The discovery of neuronal systems dedicated to computing spatial information, composed of functionally distinct cell types such as place and grid cells, combined with an extensive body of human-based behavioral and neuroimaging research has provided us with a detailed understanding of the brain's navigation circuit. In this review, we discuss emerging evidence from rodents, non-human primates, and humans that demonstrates how cognitive aging affects the navigational computations supported by these systems. Critically, we show 1) that navigational deficits cannot solely be explained by general deficits in learning and memory, 2) that there is no uniform decline across different navigational computations, and 3) that navigational deficits might be sensitive markers for impending pathological decline. Following an introduction to the mechanisms underlying spatial navigation and how they relate to general processes of learning and memory, the review discusses how aging affects the perception and integration of spatial information, the creation and storage of memory traces for spatial information, and the use of spatial information during navigational behavior. The closing section highlights the clinical potential of behavioral and neural markers of spatial navigation, with a particular emphasis on neurodegenerative disorders.